Agadi step by step : testimony of Lakshmibai Tilak in her own words - Ṭiḷaka, Lakshmībāī, 1873-1936 (M.A. Tilak, 1968)
Autobiographical reminiscenscesof a Marathi litterateur and her response to Christianity.